Assessment of pelvic floor by three-dimensional-ultrasound in primiparous women according to delivery mode: initial experience from a single reference service in Brazil - Araujo Júnior, Edward [UNIFESP] (2013)
PURPOSE: To evaluate changes to the pelvic floor of primiparous women with different delivery modes, using three-dimensional ultrasound. METHODS: A prospective cross-sectional study on 35 primiparae divided into groups according to the delivery mode: elective cesarean delivery (n=10), vaginal delivery (n=16), and forceps delivery (n=9). Three-dimensional ultrasound on the pelvic floor was performed on the second postpartum day with the patient in a resting position. A convex volumetric transducer (RAB4-8L) was used, in contact with the large labia, with the patient in the gynecological position. Biometric measurements of the urogenital hiatus were taken in the axial plane on images in the rendering mode, in order to assess the area, anteroposterior and transverse diameters, average thickness, and avulsion of the levator ani muscle. Differences between groups were evaluated by determining the mean differences and their respective 95% confidence intervals. The proportions of levator ani muscle avulsion were compared between elective cesarean section and vaginal birth using Fisher's exact test. RESULTS: The mean areas of the urogenital hiatus in the cases of vaginal and forceps deliveries were 17.0 and 20.1 cm², respectively, versus 12.4 cm² in the Control Group (elective cesarean). Avulsion of the levator ani muscle was observed in women who underwent vaginal delivery (3/25), however there was no statistically significant difference between cesarean section and vaginal delivery groups (p=0.5). CONCLUSION: Transperineal three-dimensional ultrasound was useful for assessing the pelvic floor of primiparous women, by allowing pelvic morphological changes to be differentiated according to the delivery mode.